Pengaruh Inhibitor Ekstrak Daun Inai (Lawsonia inermis L) Terhadap Laju Korosi Baja St37 dalam Larutan HCl 3% - Oricha Mutia Rani; Ediman Ginting Suka; Yanti Yulianti (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Henna leaves extract (Lawsonia inermis L) is used as a corrosion inhibitor in St37 steel soaked in 3% HCl corrosive medium. To find out the effect of inhibitor concentration on the corrosion rate of steel, the variation of inhibitor concentration is 0, 3, 5, 7 and 9%. Corrosion rate testing is done by mass loss method. Corrosion rate was tested on low carbon steel with and without inhibition of henna extract for 6 days. The results showed that the greater the concentration of inhibitor of henna extract used, the corrosion rate would decrease and the ability to inhibit corrosion would increase. The greatest corrosion efficiency occurred at a concentration of 9% with an efficiency of 88.84%. The results of X-Ray Diffraction (XRD) characterization showed that the phase formed was pure iron (Fe). Secondary Electron Microscopy (SEM) characterization showed uneven clusters and smaller sizes, holes and cracks were also less with the addition of inhibitory leaves extract than without the addition of inhibitory leaves extract. This result is reinforced by the percentage of corrosion products shown in the results of the characterization of Energy Dispersive Spectroscopy (EDS).